ADAPTING YOUR MESSAGE: NAVIGATING CONTEXT FOR TV PRESENTER SUCCESS - Mingyu, Li; Xueying , Wang; Tianyu, Wu (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
Oral communication is a critical skill for TV presenters, as it allows them to effectively convey information to their audience. This paper reviews the literature on oral communication skills for TV presenters and identifies four key areas that presenters should focus on: clarifying their thinking, combining emotions and voices, fitting the context, and standardizing their communication. The paper also provides suggestions for how presenters can improve their oral communication skills.